Estudo da enxertia hipocotiledonar do maracujazeiro-amarelo sobre dois porta-enxertos, através de microscopia eletrônica de varredura - Filho, Geraldo Costa Nogueira; Roncatto, Givanildo; Ruggiero, Carlos [UNESP]; de Oliveira, João Carlos [UNESP]; Malheiros, Euclides Braga [UNESP] (My University, 2010)
The objective of this work was to verify how much time after the accomplishment of the hypocotyledonary grafting occur the weld or the adhesion between graft and rootstock, and also the formation of the callus bridge, verified for the total fulfilling of the slot for secondary meristematic tissue (callus). It was produced 56 seedlings of yellow passion fruit (P. edulis Sims f. flavicarpa Deg.) by the hypocotyledonary grafting in full crack in the top on two rootstocks (P. edulis Sims f. flavicarpa Deg. e P. alata Dryander). On the 0, 3, 6, 9, 12, 15 and 18 days after grafting, it was collected the region of the grafting of four seedlings of each combination. The collected material was fixed in a solution of glutaraldehyde at 3%, post-fixed in osmium tetroxide at 2%, dehydrated in a series of ethyl alcohol (30, 40, 50, 60, 70, 80, 90, 100%), led to the drier of critical point (CO2), set up, metalized with gold - palladium (35 nm) and, finally, observed and eletromicrographed in a scanning electronic microscope JEOL JSM 5410 (operated at 15 kV). It was discovered that, six days after grafting, the welding for the rootstock P. alata had already occurred, which was only evidenced by P. edulis f. flavicarpa on the ninth days. Also, on the ninth day, it was observed on both rootstocks, a complete callus bridge formation, indicating that, from this point, you can start the acclimation process of the seedling, to take it to an environment of lower humidity.
Study of hypocotyledonary grafting of the passion fruit plant on two rootstocks, through scanning electronic microscopy
Keywords: Compatibility; Electromicrographic; Passiflora spp.; Sweet passion fruit plant; Vegetative propagation